2022
DOI: 10.1111/dom.14795
|View full text |Cite
|
Sign up to set email alerts
|

Real world hypoglycaemia related to glucose variability and Flash glucose scan frequency assessed from global FreeStyle Libre data

Abstract: Aim: Flash glucose monitoring provides a range of glucose metrics. In the current study, we aim to identify those that indicate that glycaemic targets can be consistently met and contrast the total (t-CV) and within-day coefficient of variation (wd-CV) to guide the assessment of glucose variability and hypoglycaemia exposure.Methods: De-identified data from Flash readers were collected. The readers were sorted into 10 equally sized groups of scan frequency followed by quartiles of estimated A1c (eA1c). A simil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…Other recent publications confirm that CV thresholds for hypoglycaemia prediction deviate from the historic 36% threshold value. Riveline et al 11 analysed data from a large intermittently scanned CGM database and noted that the CV thresholds for hypoglycaemia prediction were related to the method of calculation, specifically within day CV versus total CV (equivalent to the CV metric used in this study). When using total CV, they found a threshold of total CV <39.5% and suggested that CV <36% may not be adequate to ensure low hypoglycaemia exposure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Other recent publications confirm that CV thresholds for hypoglycaemia prediction deviate from the historic 36% threshold value. Riveline et al 11 analysed data from a large intermittently scanned CGM database and noted that the CV thresholds for hypoglycaemia prediction were related to the method of calculation, specifically within day CV versus total CV (equivalent to the CV metric used in this study). When using total CV, they found a threshold of total CV <39.5% and suggested that CV <36% may not be adequate to ensure low hypoglycaemia exposure.…”
Section: Discussionmentioning
confidence: 99%
“…When using total CV, they found a threshold of total CV <39.5% and suggested that CV <36% may not be adequate to ensure low hypoglycaemia exposure. The difference between the studies is probably related to the treatment modalities, as in Riveline et al 11 the therapies were based on non‐automated insulin systems, while the present analysis utilized data from people with type 1 diabetes treated with the MM780G system. It is possible that the findings of both analyses may be influenced by parameters such as time spent wearing the sensor; the findings of Riveline et al, however, could also potentially be influenced by other parameters such as number of scans per day.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations